Cemeteries and crematoria, forgotten public space in multicultural Europe. An agenda for inclusion and citizenship. Issue 1 (18th August 2022) - Maddrell, Avril; Beebeejaun, Yasminah; Kmec, Sonja; Wingren, Carola
Abstract: In western Europe, municipal or otherwise state‐commissioned cemeteries and crematoria are public spaces and services, open to all. Cemeteries and crematoria grounds are neglected in geographical, planning and policy debates about the character, design, management, use and accessibility of public spaces, and likewise debates about the social inclusion of migrants and minorities. This may reflect a tendency to situate cemeteries socially and geographically in the peripheries of contemporary European society, but they are, nonetheless, sites of vital public health infrastructure, as well as being highly significant symbolic, religious‐spiritual, secular‐sacred, and emotionally laden places. Examining cemeteries‐crematoria against a criteria of inclusive public space provides new insights into (1) the nature of public space and its governance; (2) rights and barriers to shared public spaces and associated infrastructure in everyday multicultural contexts; (3) national–local negotiations of majority‐minorities social relations and cultural practices in and through public spaces; and (4) the need to place municipal cemeteries‐crematoria centre stage in scholarship and policy on public space which is culturally inclusive and serves all citizens. Short Abstract: Municipal cemeteries and crematoria grounds are important but neglected spaces in geographical, Planning and policy debates about the character, design, use, governance and accessibility of public spaces. This paper highlights the political and cultural importance of cemeteries‐crematoria as public spaces, and their role in social inclusion/exclusion in multicultural and post‐secular European societies.